IS CEMENTED BIPOLAR HEMIARTHROPLASTY GOOD CHOICE FOR UNSTABLE INTERTROCHANTERIC FRACTURES IN ELDERLY: MULTICENTERIC PROSPECTIVE STUDY AT KARACHI - Muhammad Rajput , Irfan; Memon, Iftikhar; e Azam , Mohsin; Ahmed Siddiqui , Adeel; Kumar , Jagdesh; Ali , Zulfiqar; Junejo, Sadaf; Abid, Khadijah (Journal of Ayub Medical College Abbottabad, 2022)
Background: To analyse the functional outcome of primary cemented bipolar hemi arthroplasty (PCBH) for unstable osteoporotic intertrochanteric femur fractures in elderly patients. Methods: It was a multicentre prospective study conducted at Institute of Orthopaedics & Surgery, Medicare Cardiac & General Hospital and Dr Ruth K M Pfau Civil Hospital Karachi, Pakistan from February 2015 to July 2020. Thirty-eight patients of 60-90 years of either gender diagnosed as close UIF, severe osteoporosis as per Singh index grade ‰¤3, time since injury <2 weeks, ASA status II & III and pre-injury independent walking were enrolled in this study. All patients with UIF underwent PCBH. The radiographs were performed before surgery and at intervals postoperatively. All patients were requested to come for follow up visits at 2 weeks, 4 weeks, 3 months, 6 months 1 year and then at 3 years to assess the functional outcome of patients. At first postoperative day check X-rays taken and rehabilitation started as per institutional rehabilitation protocol, at 2-week stiches removed, at 4 weeks’ x-ray was done and all the patients were followed for 3 years. The primary outcomes were noted using Harris Hip Score (HHS) for the functional outcome assessed at the end of 1 year and at final follow up. Results: The mean age of the study participants was 68.29±8.04 years. One male (2.6%) died at 6th month, then 2 females (5.2%) patients died at 1 year and 2 females (5.2%) patients died at the end of 3 years due to multiple comorbid conditions. During 1st year 3 patients (7.4%) developed DVT and 4 patients (10.5%) having diabetes and hypertension developed superficial wound infection. The mean Harris Hip Score between time points which indicated that the mean Harris Hip Score significantly improve over the period of time (p=0.001). Post hoc tests revealed that there were statistically significant differences between each time points (p<0.05). The functional outcome at 3 years, shown, one patient had excellent outcome, 24 patients had good outcome and 8 had fair outcome, respectively. Conclusion: The Primary Cemented Bipolar Hemiarthoplasty is a good choice of treatment in terms of reasonable functional outcome such as early mobilization and associated with less post-operative complications in elderly patients of UIF.